O uso dos quintais produtivos pela agricultura familiar na comunidade rural João Ferreira no município de Ribeirópolis-SE - Ferreira, Ortelina Maiara Farias (2018)
The term backyard in Brazil is used to designate the spaces of the land around the residence, spaces that carry a local cultural expression as well as of natural resources of subsistence, that can be developed and cultivated both in rural localities and in periurban localities. The research of productive farms in the João Ferreira Village in Ribeirópolis / SE started from the importance of cultivating and maintaining productive farms with species of economic or food importance, maintained by the family labor force that makes up the main economic income of the family. In addition to the important role of family agriculture that drives debates on sustainable development and the generation of employment, income and food security in these small spaces. There is a need to rescue the social debt that exists with family farming resulting from modern agriculture. The purpose of this study was to analyze the use of productive farms in the rural community of João Ferreira in the municipality of Ribeirópolis-SE, and make a survey of the species cultivated in them and their uses. In order to do this, the environmental aspect of the productive backyards and their ethnobotanical knowledge was analyzed, with the identification of the species of medicinal plants present in the backyards and their uses, so that it could understand the different ways of using the yards by the farming families. As a technique of this study, qualitative and quantitative analysis was used, so that it was possible to select employees through the so-called snowball technique, to locate one or more key informants. Reaching the saturation point of the answers, that is, when they begin to repeat themselves. The methodology enriched the conceptual basis in the interpretation and validation of the results. Questionnaires were applied with 30 families, based on the first key informant, who indicated new informants. The data collected during field research showed that agricultural production is marketed by farmers in different ways. It is observed that the production systems developed in the backyards are mainly for the food crops of sweet potatoes (Ipomoea batatas), maize (Zea mays), beans (Phaseolus vulgaris), manioc (Manihot esculenta), okra (Abelmoschus esculentus), peanut (Arachis hypogaea), pepper (Capsicum annuum Group), tomato (Solanum lycopersicum), pumpkin (Cucurbita sp.), as shown in the table, as well as medicinal plants with lemongrass (Lippia alba). The economic functions of the productive backyards were shown to be of great importance both for the self-consumption of the rural farmers and for the cultivation of trees (Ruta graveolens L.). for its viability as a source of income. The economic functions of productive farms have proved to be of utmost importance both for the self-consumption of rural farmers and for their viability as a source of income.